Models and Estimation of Disequilibrium for Centrally Planned Economies - Charemza, Wojciech; Quandt, Richard E. (Review of Economic Studies, 1982)
The planned level of output is an important variable in modelling Centrally Planned Economies and the present paper discusses several disequilibrium models in which the plan level is an endogenous variable. A key relationship in such a model is the plan-adjustment equation which is the counterpart of the usual price-adjustment equation employed in models of free economies. Seemingly minor differences in assumptions lead to markedly different econometric models. The coherency properties of these are studied and several likelihood functions are derived. The most complex of the models includes both endogenous plan levels and endogenous prices.